Analisa dan Perancangan Sistem Informasi Kegiatan Pembangunan Sarana dan Prasarana Pada PNPM Mandiri Perkotaan - Taufik Hidayat (ISB Atma Luhur, 2014)
National community empowerment program (PNPM-MP) is one of the mechanisms used community empowerment program PNPM Mandiri in efforts accelerate poverty reduction and job opportunities in urban areas. Program is conducted for more encourage efforts to improve the quality of life, prosperity and independence of people in urban areas. The process of facilities and infrastructures development activities in PNPM Urban, process data collection and report activities related to Askot, For the data collection process BKM (Agency for Community Self-reliance), data collection process KSM (Self-Help Groups), process proposing activities, the statement of contribution land, assessment the list of prohibited activities (negative list), eligibility verification process of proposed activities, statement letter process capability faskel operation and maintenance of infrastructure related to residents. Process of data collection on PNPM Urban there are the manual and there are had the computerized but still using the Microsoft Word and Microsoft Excel. Because there are still manually then there is mistake in processes of facilities and infrastructure development activities.Therefore the, to resolve the problems which occur computerized systems is needed to support the progress and development of the program. With the system can resolve the problem which occurs on systems currently running.